Finn's little fibs - Percival, Tom (A big bright feelings book, 2023)
Finn has always loved going to stay with his grandma - until one day, he tells a little fib that gets out of control! This is a book about telling the truth. Be open, be honest, be you!
Keywords: valehtelu; tunteet; rehellisyys; pojat (ikäryhmät)